Potential negative effects of caffeine in athletes. - Mattioli, Anna Vittoria; Sisca, Giovanbattista; Farinetti, Alberto (Progress in Nutrition, 2019)
Letter related to “Rahimi MR, Khabiri P, Faraji H. Effects of caffeine ingestion on resistance exercise-induced apoptosis in athletes: A randomized, double-blind, placebo-controlled, crossover study. PN 2Jul.2018 [cited 20Dec.2018];20(4):563-9.”